ANALISIS PERSEPSI MASYARAKAT TERHADAP PENGGUNAAN APLIKASI TRING DI KABUPATEN ACEH JAYA: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL BERBASIS SYARIAH - Supardi Supardi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study provides empirical support for extending technology acceptance models within the context of Islamic fintech. This study aims to examine public perceptions of the Pegadaian Digital Syariah application in Aceh Jaya Regency by integrating sharia compliance into the Technology Acceptance Model (TAM) framework. A quantitative approach was employed through a survey of 90 active application users selected using purposive sampling. Data were collected using a structured questionnaire and analyzed through descriptive statistics and multiple linear regression. The results indicate that perceived ease of use, security, usefulness, and sharia compliance are positively evaluated by users and jointly have a significant effect on attitudes toward application usage. Nevertheless, the model exhibits a moderate level of explanatory power, suggesting that user acceptance is also influenced by factors beyond technical attributes, such as social influences and user experience. These findings highlight that the acceptance of sharia-based digital financial services is shaped not only by functional considerations, but also by institutional trust and perceived religious legitimacy. This study provides empirical support for extending technology acceptance models within the context of Islamic fintech.